Organocatalyzed Stereoselective Glycosylation: An Overview of the Last Decade - López, Mildred; de Parrodi, Cecilia A.; Huelgas, Gabriela; Lozada-Ramz, José Daniel (Mini-Reviews in Organic Chemistry, 2024)
Even though there has been an important evolution in the synthesis of oligosaccharides, the efficient and stereoselective study of glycosidic bonds through non-toxic, moderate, and inexpensive techniques is one of the most challenging fields in organic synthesis. Glycosyl reactions play a fundamental role in biological material and structure-activity relationships, having numerous medicinal chemistry applications. For this, interesting strategies have evolved over the years to control the stereoselectivity of glycosidic bonds, including the manipulation of different reaction elements, mainly promoters or catalysts, but also involving the nature of donors and solvents. This review looks at glycosylation methodologies in the last decade resulting in the specific formation of alpha or beta glycosidic bonds.
Keywords: catalysts